Comparison of Batang Batik Motifs with Mataram Keraton Batik and Pekalongan Batik - Monica Hartanti; Christine Claudia Lukman; Heddy Heryadi (Institut Seni Indonesia Surakarta, 2022)
Batang Batik has unique motifs that originate from its historical background as part of the Islamic Mataram Kingdom, and its geographical area adjacent to the coastal batik center of Pekalongan. Batang Keratonan Batik is influenced by the Mataram Keraton Batik, while the Batang Pesisiran Batik is influenced by the Pekalongan Batik. The influence of the Mataram Keraton Batik can be seen from the use of sogan (brown) color, as well as geometric, and organic abstract motifs, while the influence of Pekalongan Batik in the use of bright colors and figurative organic motifs. Even though they have similar designs, there are also differences between the Batang Keratonan Batik and the Mataram Keraton Batik, as well as between the Batang Pesisiran Batik and the Pekalongan Batik. The similarities and differences in visual styles are interesting to study because they show the dominance of power over aesthetic tastes from Pierre Bourdieu's concept; and the phenomenon of mimicry from the STORM theory from the study of social psychology. This research uses a qualitative descriptive approach with purposive samples originating from the Pisan Bali motif on 2 pieces of Batang Keratonan Batik and 1 piece of Mataram Keraton Batik, as well as floral and bird motifs on 1 piece of Batang Pesisiran Batik, 1 piece of Rifa'iyah Batik, and Pekalongan Batik. To reveal the similarities and differences in batik designs, we conducted a visual content analysis of color, motifs, execution of forms, layout, and composition. Furthermore, the concept of Pierre Bourdieu and the STORM mimicry theory were used to reveal the causes of the similarities and differences in visual styles of the purposive samples. The results of the analysis show that the similarities in visual style are due to the influence of power domination on aesthetic tastes in a field, and mimicry is done to gain social advantage, while the differences come from heterodoxy which occurs due to changes in the constellation of power in the social field.